Strategi Pembelajaran Public Speaking di Era Media Sosial: Peluang dan Tantangan dalam Pendidikan - Putri, Nabilla Rasikah; Al Fahmi, Faiz Fikri; Syahizafudin, Salmaa; Zahra, Raudhatul Husna Amelia; Lita, Farhah Nurul; Rahmawati, Rina (Yayasan Dharma Lentera Khatulistiwa (MALEWA), 2025)
Public Speaking is an oral communication skill that includes verbal, vocal, and visual (3V) aspects. The purpose of writing this article in general is to provide an overview and inform, provide inspiration and benefits for readers. This article can also be used to educate readers about the importance of public speaking. Public speaking includes preparation, conveying messages clearly, maintaining non-verbal communication, and overcoming anxiety and nervousness. The research method used is the library research method, which is a literature method that refers to books, articles, and journals. The results of this study show that social media is not only a communication tool, but also plays a role as a dynamic learning medium, especially in building public speaking skills. It can be concluded that learning public speaking in the era of social media requires an adaptive strategy to technological developments and the characteristics of the digital generation.